THE CONSTRUCTION OF THE DECIDENDI RATIO AND THE SIGNIFICANCE OF DISSENTING OPINION IN THE INDONESIAN CONSTITUTIONAL JUDICIAL SYSTEM - Sulaiman; Taufik Firmanto; Hajairin (Awang Long Law Review, 2026)
This study examines the construction of the ratio decidendi and the significance of the dissenting opinion in the Constitutional Court Decision Number 15/PUU-XXIII/2025 which states that the prosecutor's immunity rights as regulated in Article 8 paragraph (5) of Law Number 11 of 2021 concerning the Prosecutor's Office of the Republic of Indonesia are conditionally unconstitutional. Through a juridical-normative approach with the decision analysis method, this study aims to describe the legal arguments that form the basis of the majority decision and analyze the contribution of the dissenting opinion delivered by Constitutional Justices Arief Hidayat and M. Guntur Hamzah in enriching the discourse of constitutional law. The results of the study indicate that the ratio decidendi of this decision is built on the basis of the principle of equality before the law as guaranteed by Article 27 paragraph (1) and Article 28D paragraph (1) of the 1945 Constitution of the Republic of Indonesia, which emphasizes that legal protection for prosecutors must not be transformed into absolute immunity. The Court constructed a conditional constitutional interpretation by providing exceptions in cases of red-handed arrest, sufficient preliminary evidence, or specific criminal offenses. Meanwhile, the dissenting opinion offered an alternative perspective, viewing the provision as a functional protection mechanism for prosecutors in carrying out their duties and authorities and as part of strengthening the principle of checks and balances in the judicial system. This study concludes that the dissenting opinion has strategic significance as a living document that can serve as a reference for future legal developments, while also demonstrating the deliberative dynamics in the Constitutional Court's decision-making as the guardian of the constitution.